An Assessment of Landslides Occurrence and its Implications on the Local Community in Kanaba Sub-County Kisoro District. - Mutendereze, Edson (Kabale University, 2024)
This research assessed the occurrence and implications of landslides on the local community in Kanaba Sub-county, Kisoro District, Uganda. Despite efforts in emergency response, systematic research and comprehensive strategies to address the underlying causes and long-term impacts of landslides are limited. The study aimed to determine the relationship between landslide occurrences and their effects on the community, identifying causes, impacts, and control measures. Using a descriptive research design, data was collected through questionnaires and interviews with 66 respondents, including farmers and local officials. Key findings revealed volcanic activity as a primary cause of landslides, with significant impacts on infrastructure, agriculture, and livelihoods. The study emphasized the need for improved early warning systems, resilient infrastructure, and effective community resilience strategies. Recommendations include enhancing early warning systems, improving infrastructure resilience, and implementing proactive control measures to mitigate landslide risks and promote sustainable development practices in the region.